An Exploration of Stree Shakti Programme in Karnataka through Self-Help Groups: With Special Reference to Chitradurga District - S, Kavitha; Laxmana, P (Ushus Journal of Business Management, 2012)
For the Empowerment of women, government has come up with many schemes. Among those, Self Help Group (SHG) is found to be the strongest route. The purpose of the Programme is to endow women economically and socially by bringing them in self-help groups, and it spent corers of rupees at a time in the project taken up for the development of women and organizing women empowerment in such huge number.